2012
DOI: 10.1021/ja212188r
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Epimerization of Glycosylated Amino Acids During Solid-Phase Peptide Synthesis

Abstract: Glycopeptides are extremely useful for basic research and clinical applications, but access to structurally-defined glycopeptides is limited by the difficulties in synthesizing this class of compounds. In this study, we demonstrate that many common peptide coupling conditions used to prepare O-linked glycopeptides result in substantial amounts of epimerization at the alpha position. In fact, epimerization resulted in up to 80% of the non-natural epimer, indicating that it can be the major product in some react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 63 publications
0
65
0
Order By: Relevance
“…We employed coupling conditions that were determined previously by our laboratory to minimize racemization of the α-carbon of the amino acid. 85,86 Final stages for the preparation of the desired AuNP ligand included Fmoc deprotection with piperidine, acetylation of the resulting amino group with acetic anhydride in methanol and Zemplèn deprotection of all O- and S-protected acetates resulting in thiols 10a and 10b . For the preparation of the control ligand, compound 2 was processed directly to the thioacetate 11 and hydrolyzed to 12 ; this compound was used directly for AuNP synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…We employed coupling conditions that were determined previously by our laboratory to minimize racemization of the α-carbon of the amino acid. 85,86 Final stages for the preparation of the desired AuNP ligand included Fmoc deprotection with piperidine, acetylation of the resulting amino group with acetic anhydride in methanol and Zemplèn deprotection of all O- and S-protected acetates resulting in thiols 10a and 10b . For the preparation of the control ligand, compound 2 was processed directly to the thioacetate 11 and hydrolyzed to 12 ; this compound was used directly for AuNP synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of COMU ( 16 ) and Oxyma ( 15 ) is an alternative to maintain acceptable epimerization levels, which can also be used to decrease the risk of guanidylation. Moreover, COMU ( 16 ) and Oxyma ( 15 ) mixtures are reported to display higher acylation capacity than HDMA ( 11 )/HOAt ( 2 ) and HCTU ( 6 )/HOAt ( 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we recently demonstrated that many commonly used peptide coupling conditions produce high levels of epimerization for glyco-amino acids. 11 In fact, epimerization could produce as high as 80% of the unnatural epimer. At present, however, the factors that influence efficiency and epimerization are not well understood, and additional studies are needed to develop efficient and general peptide coupling conditions for glycopeptides.…”
mentioning
confidence: 99%
“…11 In this study, we evaluated efficiency and epimerization when coupling glycosylated threonine derivatives. Non-glycosylated threonine derivatives are known to react more slowly than the corresponding serine derivatives in solid phase peptide coupling reactions.…”
mentioning
confidence: 99%